Anti–Blood Group Antibodies in Intravenous Immunoglobulin May Complicate Interpretation of Antibody Titers in ABO‐Incompatible Transplantation. Issue 8 (17th March 2016) - Staley, E. M.; Carruba, S. S.; Manning, M.; Pham, H. P.; Williams, L. A.; Marques, M. B.; Locke, J. E.; Lorenz, R. G.
Abstract : Patients receiving ABO‐incompatible (ABOi) kidney transplants are treated before and after transplant with combination therapy, such as intravenous immunoglobulin (IVIG) and therapeutic plasma exchange, to prevent allograft rejection by reducing anti‐A and anti‐B titers. Although generally considered safe, it is well known that commercial IVIG products contain detectable anti‐A and anti‐B, which can be associated with hemolysis. Different preparative manufacturing techniques during the production of IVIG affect ABO antibody levels in IVIG preparations; therefore, some manufacturers now use new methods to reduce anti‐A/B levels at the preproduction stage. The variations in implementing these strategies creates the potential for significant variation in antibody titers between products and, in some cases, even between lots of the same IVIG product. We report a case of persistently elevated anti‐A titers in an ABOi kidney transplant recipient associated with elevated ABO antibody titers present in the preparation of IVIG used at our facility. Abstract : The authors provide evidence that the presence of anti–blood group antibodies in commercially available preparations of intravenous immunoglobulin can complicate the interpretation of anti–blood group antibody titers in the setting of incompatible organ transplantation.